Budd-Chiari syndrome in Behcet's disease: a retrospective multicenter study - Akyol, Lutfi; Toz, Bahtiyar; Bayindir, Ozun; Zengin, Orhan; Cansu, DonduUskudar; Yigit, Murat; Sayarlioglu, Mehmet (Springer London Ltd, 2022)
Objective To compare the clinical features, laboratory findings, and prognosis of Behget's disease (BD) patients with and without Budd-Chiari syndrome (BCS). Methods This multicenter retrospective study investigated 61 (M/F: 41/20) patients with BD, having coexistent BCS, and 169 (M/F:100/69) BD patients as the control group without BCS from 22 different centers of Turkey diagnosed between 1990 and 2017. Results Of the total 61 BD patients with BCS, the onset of the first symptom and the median age of diagnosis were earlier in contrast to BD patients without BCS (p = 0 .005 and p = 0 .007) . Lower extremity deep vein and inferior vena cava (IVC) thrombosis were more common in patients with BCS (all; p < 0.01) compared to the control group. Mortality was significantly higher in BD-BCS patients with IVC thrombosis than in the controls (p = 0 .004) . Since most of the cases in our cohort had chronic and silent form of BCS, mortality rate was 14.8%, which was on the lower range of mortality rate reported in literature (14-47%). While all BD-BCS patients received immunosuppressive (IS) agents, only half of them received additional anticoagulant treatments. Among IS agents, interferon treatment was more frequently used in this cohort (19%), compared to other series reported in literature (2.3%). Conclusion To our knowledge, this is the largest series of BD patients with BCS. Our patients had earlier disease onset and diagnosis, higher frequency of IVC thrombosis, and higher mortality rate, compared to BD patients without BCS. Mortality was significantly higher in BD-BCS patients with IVC thrombosis compared to controls.
Keywords: Behcet's disease; Budd-Chiari syndrome; Inferior vena cava; Prognosis; Thrombosis